MANAJEMEN TRANFORMASI PENDIDIKAN ISLAM: INTEGRASI NILAI SPIRITUAL DAN TEKNOLOGI DALAM LEMBAGA PENDIDIKAN - Achmad Faizal Ababil; Abdullah Abdullah; Nur Widyasari; Zaiton Binti Mustafa (Jurnal Manajemen Pendidikan, 2026)
This research aims to analyze the management of Islamic education transformation thru the integration of spiritual values and technology in the management of educational institutions. The phenomenon under study focuses on the challenges of digitalization that could potentially weaken spiritual values, as well as the institution's efforts to balance technological efficiency with spiritual development. This research approach uses a multi-case qualitative method, with the research subjects consisting of school principals, teachers, and educational staff at two Madrasah Aliyah in Banyuwangi. Data was collected thru in-depth interviews, participant observation, and document analysis, and then analyzed using the interactive model of Miles and Huberman. The research findings indicate that the integration of spirituality and technology is realized thru trust-based value management, ethics-oriented digital training, and the strengthening of a spiritual work culture. This research concludes that digital transformation based on faith and morals is capable of strengthening the professionalism and institutional character of Islamic education.